Challenges in assigning endocrine‐specific modes of action: Recommendations for researchers and regulators. (3rd February 2017) - Mihaich, Ellen M; Schäfers, Christoph; Dreier, David A; Hecker, Markus; Ortego, Lisa; Kawashima, Yukio; Dang, Zhi‐Chao; Solomon, Keith
ABSTRACT: As regulatory programs evaluate substances for their endocrine‐disrupting properties, careful study design and data interpretation are needed to distinguish between responses that are truly endocrine specific and those that are not. This is particularly important in regulatory environments where criteria are under development to identify endocrine‐disrupting properties to enable hazard‐based regulation. Irrespective of these processes, most jurisdictions use the World Health Organization/International Programme on Chemical Safety definition of an endocrine disruptor, requiring that a substance is demonstrated to cause a change in endocrine function that consequently leads to an adverse effect in an intact organism. Such a definition is broad, and at its most cautious might capture many general mechanisms that would not specifically denote an endocrine disruptor. In addition, endocrine responses may be adaptive in nature, designed to maintain homeostasis rather than induce an irreversible adverse effect. The likelihood of indirect effects is increased in (eco)toxicological studies that require the use of maximum tolerated concentrations or doses, which must produce some adverse effect. The misidentification of indirect effects as truly endocrine mediated has serious consequences for prompting animal‐ and resource‐intensive testing and regulatory consequences. To minimize the risk for misidentification, an objective and transparent weight‐of‐evidence procedure based on biological plausibility, essentiality, and empirical evidence of key events in an adverse outcome pathway is recommended to describe the modes of action that may be involved in toxic responses in nontarget organisms. Confounding factors such as systemic toxicity, general stress, and infection can add complexity to such an evaluation and should be considered in the weight of evidence. A recommended set of questions is proffered to help guide researchers and regulators in discerning endocrine and nonendocrine responses. Although many examples provided in this study are based on ecotoxicology, the majority of the concepts and processes are applicable to both environmental and human health assessments. Integr Environ Assess Manag 2017;13:280–292. © 2016 SETAC Key Points: An objective and transparent weight‐of‐evidence procedure based on biological plausibility, essentiality, and empirical evidence of key events in an adverse outcome pathway is recommended to describe the modes of action that may be involved in toxic responses in nontarget organisms. Mechanistically linking key events along a proposed endocrine‐specific adverse outcome pathway is the first step in establishing biological plausibility for a suspected endocrine‐active substance to cause adverse apical effects. Examples are given on how systemic toxicity, infection, general stress, and nutritional status can confound, limit, or influence the assessment of whether adverse effects are a consequence of an endocrine mode of action. Questions were developed to help guide researchers and regulators in the evaluation process to resolve whether a chemical has an endocrine‐specific mode of action resulting in adverse effects.